Configuration and Application of ROADM in Optical Layer Networking - Chunhua Zhao (Dianxin kexue)
Various kinds of configuration of reconfigurable optical add-drop multiplexer（ROADM）were illustrated.Differences in application between optical cross-connect and electrical cross-connect were compared.The main application of ROADM in carrier's network was presented.The scalability of the structure on CDC based ROADM was analyzed.A future framework of CDC based ROADM was proposed and its application in the optical layer and the electrical layer combined networking was analyzed.